Використання інтерактивних технологій як важлива педагогічна умова формування професійного іміджу майбутніх соціальних працівників - Остапйовський, Ігор Євгенович; Ostapiovskyi, Ihor Ye. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розкрито актуальність проблеми формування професійного іміджу майбутніх соціальних працівників. Дано визначення професійного іміджу. Розкрито сутність та ґенезу інтерактивних технологій. Здійснено порівняльний аналіз традиційного навчання та інтерактивного. Проаналізовано особливості використання різноманітних інтерактивних методів у формуванні професійного іміджу соціальних працівників.The topicality of the problem is grounded in the article. The definition of the professional image of the future social workers are formulated according to the results of the research. It is the image of a professional specialist, which was formed in the minds of students. It includes two parts: an external (appearance of the future of the social worker and his use of verbal and non-verbal means of communication) and internal (personal qualities and knowledge, skills associated with obtaining professional qualification) and their ability to present it for the create a positive perception of the future expert students, teachers, prospective clients, employers and the environment. The process of forming professional image of the future social workers consider the unity of three components: motivation (the desire to create a professional image); cognitive (knowledge of students about the image); the activity (application of knowledge and motivation in practice). Some stages are defined in accordance to the components : propedeutics, main and final. They are cross-cutting and going from the beginning to the completion of university studies. It is proved that interactive technologies are an important condition for the formation of professional pedagogical image of the future social workers have.
Using interactive technology as an important pedagogical conditions of formation of professional image of the future social workers
Keywords: соціальний працівник; імідж; професійний імідж; педагогічні умови; інтерактивні технології; social worker; image; professional image; pedagogical conditions; interactive technology